2012
DOI: 10.1557/jmr.2012.137
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen in oxide semiconductors

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 110 publications
6
67
0
1
Order By: Relevance
“…This is concluded from the different annealing behavior of the SPV samples with and without an a-Si:H (i) buffer (not shown) and from the fact that our ITO and aluminum doped zinc oxide (AZO) films (also high band gap n-type metal oxide) are also strongly modified by the hydrogen from the a-Si:H [33,34]. That hydrogen can play a vital role for such material systems is also expected from literature [35].…”
Section: J-v and Suns-v Oc Parametersmentioning
confidence: 53%
“…This is concluded from the different annealing behavior of the SPV samples with and without an a-Si:H (i) buffer (not shown) and from the fact that our ITO and aluminum doped zinc oxide (AZO) films (also high band gap n-type metal oxide) are also strongly modified by the hydrogen from the a-Si:H [33,34]. That hydrogen can play a vital role for such material systems is also expected from literature [35].…”
Section: J-v and Suns-v Oc Parametersmentioning
confidence: 53%
“…In recent studies, however, hydrogen impurities have been found to be the dominant shallow donors in several important cases. [5][6][7][8][9][10] In 2 O 3 , a prototypical transparent conducting oxide, has the cubic bixbyite structure with a conventional unit cell that contains 80 atoms. 11 The oxygen sites are all equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually assumed that information obtained from μSR can be transferred with appropriate modifications to H. However, overlapping experiments to support this assumption are scarce. A particularly relevant case is the doping character of H in semiconductors and oxides [3][4][5][6], where practically all calculations refer to the electronic structure of H whereas most experimental information comes from μSR [7][8][9][10][11][12][13]. Overlapping data exist only for ZnO where proton-ENDOR (electron-nuclear double resonance) data [14] can be compared directly with μSR results [15][16][17][18].…”
mentioning
confidence: 99%
“…The gradual population of the excited state with increasing temperature and rapid fluctuations between neighboring bonding sites lead to the collapse of the hyperfine interaction. These site changes occur within the same oxygen channel and on a single TiO 6 sublattice. The present data indicate an energy difference of about 0.9(1) meV between the ground state and excited state.…”
mentioning
confidence: 99%